The genre of suffering in the ancient Near Eastern literature, the Hebrew Bible, and in some examples of modern literature - Middlekoop, Roeland (Department of Religious Studies, 2020)
The aim of this thesis is to compare works of drama regarding the suffering of the human being in the context of life and literature and in relation to the issue of justice, which revolves around the impact of Justice, Humanity and God. My aim is to look at the development of the genre of suffering starting with the Ancient Near Eastern Literature, to define the genre in its development and to characterise its features in the various literatures discussed, especially with respect to the Book of Job.